BOTTOM-UP AND TOP-DOWN LISTENING PROCESSES WITHIN COGNITIVE CONSTRUCTIVIST LEARNING THEORY - titis sulistyowati (Universitas Muria Kudus, 2019)
The attention in Listening processes has switched from the text to the listener, from the process of identification to the process of understanding, and from the decontextualized memorization of definitions to developing language competence of students. This conception is then supported by the theory of congnitive constructivism which sees learning as the process of constructing new knowledge. This paper aims to explore activities which can be applied to develop listening language skills in a context of authentic learning within constructivist learning approach. The learning activity will be based on the features of constructivism which views learning as an active process and knowledge is not absorbed passively but it is invented by the learners. By integrating the top-down and bottom-up listening processes and cognitive constructifist learning activities, this process will facilitate students in elaborating their previous knowledge and constructing new knowledge.